2010
DOI: 10.1037/a0021383
|View full text |Cite
|
Sign up to set email alerts
|

A school-randomized clinical trial of an integrated social–emotional learning and literacy intervention: Impacts after 1 school year.

Abstract: Objective: To report experimental impacts of a universal, integrated school-based intervention in socialemotional learning and literacy development on change over 1 school year in 3rd-grade children's socialemotional, behavioral, and academic outcomes. Method: This study employed a school-randomized, experimental design and included 942 3rd-grade children (49% boys; 45.6% Hispanic/Latino, 41.1% Black/African American, 4.7% non-Hispanic White, and 8.6% other racial/ethnic groups, including Asian, Pacific Island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(99 citation statements)
references
References 66 publications
4
89
0
4
Order By: Relevance
“…73 However, others have suggested that the optimal time for depression prevention programmes may actually be in late childhood (9-10 years of age). [74][75][76] Finally, preventing depression in adolescents is challenging. It is a complex problem, in which genetic and developmental factors, the role of puberty and sex hormones, and psychosocial stress and adversity all play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…73 However, others have suggested that the optimal time for depression prevention programmes may actually be in late childhood (9-10 years of age). [74][75][76] Finally, preventing depression in adolescents is challenging. It is a complex problem, in which genetic and developmental factors, the role of puberty and sex hormones, and psychosocial stress and adversity all play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown wide applications for in-person SST programs (e.g., a trained provider implementing a program within small groups of 6-8 children), from assisting young children with developing self-awareness and emotion regulation skills (Moreira et al 2010) to helping children with attention problems learn better self-management strategies (Raimundo et al 2013) to promoting social problem-solving skills and adaptive social behavior among children with autism spectrum disorder (Mathews et al 2013;Reichow and Volkmar 2010;Scattone et al 2006). In addition to its use with specific populations of children, research supports the benefits of SST as a universal, integrated intervention approach by which all children participate in social emotional learning, regardless of diagnosis or special education status, and thereby all children can benefit from enhanced social skills and a more positive overall school climate (e.g., Jones et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Previous research shows that other school-based social-emotional programs are consistently integrated into routines (i.e. Frey, Nolen, Edstrom, & Hirschstein, 2005;Jones, Brown, Hoglund, & Aber, 2010;Webster-Stratton, Reid, & Stoolmiller, 2008). Therefore, implementation of MindMasters 2 may be more effective if used on a regular basis.…”
Section: Discussionmentioning
confidence: 99%